Exchange Rates, Interest Rates (BI Rate), World Gold Prices, and the Dow Jones Index to the Composite Stock Price Index (JCI): Nilai Tukar, Tingkat Suku Bunga (BI Rate), Harga Emas Dunia, dan Indeks Dow Jones Terhadap Indeks Harga Saham Gabungan (IHSG) - Faudina, Nur Amaliatus; Sriyono, Sriyono (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the influence of exchange rates, interest rates (BI Rates), World Gold Prices and The Dow Jones Index on the Composite Stock Price Index (CSPI). The approach used in this research is the quantitative approach. The population in this study is the Composite Stock Price Index (CSPI) listed on the Indonesia Stock Exchange. The data used in this study is secondary data in the form of time series with the period January 2019 – June 2021. The sampling technique uses a saturated sampling method where the entire population in the study is used as a sample, where in this study the data is taken every week with a sample count of 131. The data analysis in this study used eviews-10. The results of this study showed that the Exchange Rate, Interest Rate (BI Rate), World Gold Price and Dow Jones Index simultaneously had a significant effect on the Composite Stock Price Index (CSPI). The World Gold Price and The Dow Jones Index partially had a significant and positive effect on the Composite Stock Price Index (CSPI). while the Exchange Rate and Interest Rate (BI Rate) have no significant effect on the Composite Stock Price Index (CSPI).